German ex-soldiers being the guest of the British legion branch in Brighton; the mayor wellcoming Klein Korres. From: Keesings Wereldgebeuren in Beeld
German ex-soldiers being the guest of the British legion branch in Brighton; the mayor wellcoming Klein Korres. From: Keesings Wereldgebeuren in Beeld.